The Lonesome Death of Alexander Reder, Alien Cloakmaker - Tucker, Eric (The Beaver, 1999)
By the end of the nineteenth century politicians could no longer overlook the demands of the burgeoning labour movement. New laws began to set minimum standards in employment. One act protected striking Canadian workers by preventing employers from hiring across the line in the U.S. On paper it looked like progressive legislation. But when it came time to put the law into practice, there was an absence of will. Not even a tragic suicide could change the status quo. –Introduction